Genomics as part of an integrated study of smallholder sheep farming systems in the Western Cape, South Africa - Molotsi, Annelin Henriehetta (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.